Influence of local structure and metal-oxygen hybridization on the electrical and magnetic properties of alkaline earth metal (Mg2+, Ca2+, Sr2+) substituted LaFeO3 ceramics - Nandy, Subhajit; Theingi, Mya; Ghosh, Sayan; Chae, Keun Hwa; Sudakar, C. (American Institute of Physics, 2024)
Pristine and alkaline-earth metal-substituted LaFeO3 (La(1-x)A(x)FeO(3-delta); x = 0 and 0.2; A = Mg2+, Ca2+, and Sr2+) sintered ceramics are prepared from nanoparticles synthesized via a low-temperature citrate sol-gel technique. X-ray diffraction studies confirm the formation of a phase-pure LaFeO3 structure without any secondary phases for all the La(1-x)A(x)FeO(3-delta) compositions. LaFeO3 and La(0.8)Mg(0.2)FeO(3-delta )ceramics show Raman active modes related to La vibration, oxygen octahedral tilting, bending, and stretching. The optical bandgap is estimated to be 2.34 eV for pure LaFeO3 and reduces to 2.23 eV for La0.8Mg0.2FeO3-delta ceramics. On the contrary, La0.8Ca0.2FeO3-delta and La0.8Sr0.2FeO3-delta ceramics show no features in Raman spectra, consistent with the observation of metallic nature and diffuse band edge without any indication of sharp band edge noted. X-ray absorption spectroscopy (XAS) studies on La-L-3 and Fe-K-edges confirm the oxidation states of La3+ and Fe3+ in all these ceramics. Local structural distortions and formation of oxygen vacancies in La(0.8)A(0.2)FeO(3-delta) (A = Mg2+, Ca2+, and Sr2+) ceramics are discerned from XAS structure analysis compared to the pristine LaFeO3 ceramics. Magnetic measurements of La(1-x)A(x)FeO(3-delta )reveal weak ferromagnetic nature except for La0.8Mg0.2FeO3-delta, which shows a large magnetization of 4.6 (6.7) emu/g at 300 (5) K. The ferromagnetic behavior of La0.8Mg0.2FeO3-delta ceramics seems to originate from the modification of hybridization between Fe(3d)-O(2p), La(5d)-O(2p), and Fe(4sp)-O(2p) orbitals. An anomalous magnetic transition observed only in zero-field-cooled curves at 88 K in La0.8Ca0.2FeO3-delta and La0.8Sr0.2FeO3-delta ceramics is correlated to the formation of new electronic states containing O 2p character as discerned from pre-peak O-K-edge.